If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -6 = 12y Reorder the terms: -6 + -4x = 12y Solving -6 + -4x = 12y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -4x = 6 + 12y Combine like terms: -6 + 6 = 0 0 + -4x = 6 + 12y -4x = 6 + 12y Divide each side by '-4'. x = -1.5 + -3y Simplifying x = -1.5 + -3y
| 4(x)+2(23-x)=62 | | k-20=-40 | | 4x-6=12y | | 9.8x+2.4y-8.1=0 | | -20+a=-2 | | -25=-16+N | | 4sin(0)= | | f(x)=2x^2-12x-27 | | 3k^2+16k+16=0 | | g(f(x))=h(g(x)) | | 11x+3=-25 | | -6w-2(-2x+5w)+5x= | | -4(v-1)=5v-32 | | 20k+20=-20+18k | | 5x-4=5(x-2) | | h^2-8h-9=0 | | 2X-4=4y | | -7u-35=7(u-7) | | 2.7x+6.1+3.2-4.9= | | 2[x+4]=-5x+1 | | 7w-1=14+1+7w | | 8+3x=4x+5+2 | | 10x-2y=0 | | 5d^2+46d+9=0 | | xp+xq=r | | -7(u-5)=-3u+3 | | -8-9z=-3-10z | | 5x+6=10y | | 8s^2+33s+4=0 | | 2x+y=7*y | | 6-6h=10-4h | | 4u+16=72 |